Heterogeneous differentiation patterns of individual CD8+ T cells - Gerlach, Carmen; Rohr, Jan C; Perié, Leïla; van Rooij, Nienke; van Heijst, Jeroen W J; Velds, Arno; Urbanus, Jos; Naik, Shalin H; Jacobs, Heinz; Beltman, Joost B; de Boer, Rob J; Schumacher, Ton N M (Science (American Association for the Advancement of Science), 2013)
Upon infection, antigen-specific CD8(+) T lymphocyte responses display a highly reproducible pattern of expansion and contraction that is thought to reflect a uniform behavior of individual cells. We tracked the progeny of individual mouse CD8(+) T cells by in vivo lineage tracing and demonstrated that, even for T cells bearing identical T cell receptors, both clonal expansion and differentiation patterns are heterogeneous. As a consequence, individual naïve T lymphocytes contributed differentially to short- and long-term protection, as revealed by participation of their progeny during primary versus recall infections. The discordance in fate of individual naïve T cells argues against asymmetric division as a singular driver of CD8(+) T cell heterogeneity and demonstrates that reproducibility of CD8(+) T cell responses is achieved through population averaging.